2017
DOI: 10.1161/circulationaha.117.027834
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lifelong Exercise Volume and Coronary Atherosclerosis in Athletes

Abstract: Participants in the >2000 MET-min/wk group had a higher prevalence of CAC and atherosclerotic plaques. The most active group, however, had a more benign composition of plaques, with fewer mixed plaques and more often only calcified plaques. These observations may explain the increased longevity typical of endurance athletes despite the presence of more coronary atherosclerotic plaque in the most active participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
166
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(191 citation statements)
references
References 51 publications
13
166
2
10
Order By: Relevance
“…Along these lines, recent studies in healthy middle-age highly-active adults have reported that higher doses of exercise were associated with higher levels of CAC and that the atherosclerotic plaques were in fact likely to be more calcified plaques, suggesting that the stable nature of coronary plaques in highly active individuals may mitigate plaque rupture. 41,42 Additional research investigating whether higher PA levels, including type and duration of PA, are associated with increased plaque calcium density for a given CAC volume, indicative of plaque stability to evaluate CV risk, is needed. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, recent studies in healthy middle-age highly-active adults have reported that higher doses of exercise were associated with higher levels of CAC and that the atherosclerotic plaques were in fact likely to be more calcified plaques, suggesting that the stable nature of coronary plaques in highly active individuals may mitigate plaque rupture. 41,42 Additional research investigating whether higher PA levels, including type and duration of PA, are associated with increased plaque calcium density for a given CAC volume, indicative of plaque stability to evaluate CV risk, is needed. 43 …”
Section: Discussionmentioning
confidence: 99%
“…In general, runners have a 25%–40% reduced risk of premature mortality and live approximately 3 years longer than non-runners 43. Although high lifelong exercise volume among surviving athletes is associated with coronary artery calcifications, the atherosclerotic plaques of the most active athletes have a more benign composition 44. The evidence is mostly based on observational follow-up studies, one limitation of which is the difficulty of controlling for genetic or other selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several groups have reported a prevalence of coronary artery disease (CAD) of 40-63% in master athletes. [10][11][12] We have reported elevated post-exercise cTn values following strenuous exercise in asymptomatic subjects with occult CAD. 6 Subjects included in the present study were 50-74 years of age.…”
mentioning
confidence: 94%